2020
DOI: 10.1080/2331205x.2020.1757184
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and motivators to participation in hand washing promotion programs at household level among refugees in Rhino Settlement, Arua District _ Uganda

Abstract: Introduction: The major aim of hand washing promotion programs is to persuade people to change their behaviour to reduce high-risk hygiene practices and use. Unfortunately, in a refugee setting, there is a dearth of information about participation in hand washing promotion programs. Objective: To assess barriers and motivators to participation in hand washing promotion programs at household level among refugees in Rhino Camp, Arua district, Uganda. Methods: A crosssectional study was conducted to collect quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…This is because availability of hand hygiene facilities in places where hand hygiene must be practiced increases the opportunity of practicing it. Earlier studies revealed that having hand hygiene facilities with water and soap at critical points increases their utilisation, and consequently hand hygiene practice (Namara et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is because availability of hand hygiene facilities in places where hand hygiene must be practiced increases the opportunity of practicing it. Earlier studies revealed that having hand hygiene facilities with water and soap at critical points increases their utilisation, and consequently hand hygiene practice (Namara et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…52.8% (159/301) for sometimes, 1% (3/301) for always, 10% (30/301) for most of the time, 4.7% (14/301) for never and 31.6% (95/301) for rarely. About 20.9% (391/1869) of the respondents had visited a dentist at least once in the last 12 months.…”
mentioning
confidence: 98%
“…Three studies mentioned that the social pressures exerted by community members motivated handwashing. It was found that conforming to hand hygiene rules in churches in the Democratic Republic of the Congo was done to maintain a good image; moreover, in Uganda, households observed to perform correct handwashing practices by neighbors influenced them to do the same [ 19 , 31 ]. In addition, children reminding their mothers to wash their hands acted as a form of social influence, facilitating handwashing behavior [ 53 ].…”
Section: Theoretical Domains Framework (Tdf)mentioning
confidence: 99%
“…Twenty-two of the 46 studies identified multiple barriers to hand hygiene because of the environmental context and resources. Most prominently, 11 studies found that the lack of handwashing resources limited the ability to carry out proper hand hygiene [ 19 , 22 24 , 27 , 28 , 30 , 31 , 40 , 41 , 61 ], due to the lack of handwash station hardware and water supply and its quality, multiuse of soap for both handwashing and laundry, and soap shortages [ 19 , 22 24 , 27 , 28 , 30 , 31 , 39 41 ]. Nine studies found that a high cost of materials and a low budget placed financial restraints on hand hygiene [ 17 , 19 , 22 , 30 , 34 , 35 , 41 , 42 , 45 ].…”
Section: Theoretical Domains Framework (Tdf)mentioning
confidence: 99%